Nurses' Knowledge, Attitudes, and Practice of Cardiopulmonary Resuscitation at a Selected Training Hospital in Namibia: A Cross-Sectional Survey - Nestor Tomas RN, RM, RCN, RT, MPH; Zuze A. Kachekele RN, RM (SAGE Publishing, 2023)
Background Nurses play a key role in cases of cardiopulmonary arrest by promptly attending to and initiating cardiopulmonary resuscitation. Effective cardiopulmonary resuscitation thus requires nurses to possess appropriate attitudes, competencies, and adherence to the best nursing practice. Cardiac arrests are a prevalent cause of fatalities, being responsible for approximately 30% of deaths worldwide. Despite this statistic, however, research in this specific field is lacking in Namibia. Objective The objective of this research was to examine registered nurses' knowledge, attitudes toward, and practice with regard to cardiopulmonary resuscitation at a selected teaching hospital in Namibia. Methods A cross-sectional survey design using a self-administered questionnaire was utilized to purposively recruit 158 registered nurses from the inpatient and outpatient departments of a teaching hospital in Namibia. Descriptive and chi-square tests were performed using SPSSv26. Results The results of the study indicate that a significant percentage of nurses have limited knowledge (14.7 ± 1.50), negative attitudes (36.2 ± 4.8), and poor practice (11.16 ± 1.18) when it comes to cardiopulmonary resuscitation. Their poor knowledge is strongly associated with poor practice (χ 2  = 9.162, P  = .002). The study further revealed a significant correlation between the departments in which the nurses worked and their practice of cardiopulmonary resuscitation, suggesting that the work environment is a crucial factor in determining a nurse's approach to emergency care. Conclusion The findings of study indicate that the cardiopulmonary resuscitation practice in the selected hospital is unsafe due to the registered nurses' poor knowledge and negative attitudes. It is strongly recommended that hospital managers and policy-makers take steps to formulate guidelines that mandate regular cardiopulmonary resuscitation training at predetermined times.